DOI: 10.11606/d.22.2009.tde-18082009-130259
|View full text |Cite
|
Sign up to set email alerts
|

Direitos dos usuários com Diabetes Mellitus: do conhecimento à utilização dos benefícios na saúde

Abstract: Aos meus pais, Henrique e Leny Aos meus irmãos, Maico e Tiago Aos meus avós, Tunico e Ilza À minha afilhada Maysa Eduarda Não tenho palavras capazes de expressar o que vocês representam em minha vida. Vocês, que sempre estiveram ao meu lado, entendendo minhas constantes e necessárias ausências, meu mau humor. Vocês, que compartilharam comigo meus momentos de indecisão, de angústia, de tristezas, de alegrias, de conquistas... Vocês, que sempre me apoiaram, incentivaram e me empurraram para frente quando as forç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
3
0
3
Order By: Relevance
“…In relation to the educational level, more than half had only completed Incomplete Elementary School (7); Two others attended high school; Two users were illiterate and one had completed Full Higher Education. With regard to marital status, the majority were married or lived in a stable union (10). It was observed that a large part of the interviewees did not perform formal work activities only performing domestic services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the educational level, more than half had only completed Incomplete Elementary School (7); Two others attended high school; Two users were illiterate and one had completed Full Higher Education. With regard to marital status, the majority were married or lived in a stable union (10). It was observed that a large part of the interviewees did not perform formal work activities only performing domestic services.…”
Section: Resultsmentioning
confidence: 99%
“…This gives continuity to a process of high costs, but that does not reach its main objectives. 10 Therefore, for the proper accomplishment of the AMGC, it is necessary that the continuing education program be a priority as established by the legislation, before adhering to the distribution of glymeters for the population, since the health professional, when performing the follow-up of the user, will provide the tools Necessary for the user to acquire the knowledge essential for a CBA that results in improvement of the clinical condition of the same and thus prevent or minimize acute and chronic complications.…”
Section: Category 1: Realization Of the Amgc In A Non-rational Waymentioning
confidence: 99%
“…57 Ainda, outro trabalho aponta que o autocuidado vai além da terapêutica, engloba a percepção do usuário com DM tipo II acerca de seu papel como cidadão. 58 Desse modo, o conhecimento em relação aos seus direitos e benefícios da legislação pode contribuir com a efetivação do exercício da autonomia do usuário com diabetes.…”
Section: Resultsunclassified
“…Além disso, possui uma gestão descentralizada para os municípios e tem como porta de entrada a atenção primária, por meio da estratégia de saúde da família (ESF). 7 A ESF foi implantada, a partir de 1994, com o objetivo de ampliar a atenção primária em saúde (APS) e reordenar a prática assistencial. 8 Entre as responsabilidades do nível primário de atenção está o diagnóstico, o tratamento e o acompanhamento dos portadores de DM.…”
Section: Introductionunclassified